Training and Development for Library and Media Teachers in Selected Malaysian School Resource Centres - Kamal, M. A; Normah, Othman (2012)
Training and development for library and media teachers is used as means of achieving positive outcome results in school resource centre. However, it appears that many educational organisations in Malaysia including school resource centre have not paid sufficiently close attention to training and career development of their human resources, leading to an under-utilisation of talent in the organisation. This study investigated the training and development practices at school resource centre. A questionnaire-based survey was carried out among a sample of the library media teachers in the Kemaman district of Malaysia. The study, which was aimed to investigate the training and development of human resource in school resource centre revealed that even though respondents were aware of and had appreciable knowledge of the policy, the fact that the training policy has not been formally instituted and implemented shows a lack of commitment on the part of the management of school authority towards developing its human resource at school resource centre. The training and development procedures at school resource centre have no standard practices. However, the relevance and effectiveness of the methods used were successful in equipping the library and media teachers with the required skills for their work.